A child's world : infancy through adolescence - Martorell, Gabriela. 4 0 16; Papalia, Diane E.,;Feldman, Ruth Duskin; 5 (New York : McGraw-Hill Education, 2013)
This edition continues to provide the extensive cross-cultural and multicultural coverage, the innovative pedagogical learning system, and the balance between research and real-life applications that has made this title a favorite of students and professors alike. The new edition was revised using McGraw-Hill's Heat Map Technology, which gives authors access to real data from real students to create their revisions. This data is anonymously collected from the many students who use LearnSmart, the adaptive learning tool that provides students with an individualized assessment of their own progress. Because virtually every text paragraph is tied to several questions that students answer while using LearnSmart, empirical data showing the specific concepts with which students have the most difficulty is easily pinpointed for the authors to review.
About the authors -- Preface -- Entering a child's world -- Studying a child's world -- A child's world : how we discover it -- Beginnings -- Forming a new life : conception, heredity, and environment -- Pregnancy and prenatal development -- Birth and the newborn baby -- Infancy and toddlerhood -- Physical development and health during the first three years -- Cognitive development during the first three years -- Psychosocial development during the first three years -- Early childhood -- Physical development and health in early childhood -- Cognitive development in early childhood -- Psychosocial development in early childhood -- Middle childhood -- Physical development and health in middle childhood -- Cognitive development in middle childhood -- Psychosocial development in middle childhood -- Adolescence -- Physical development and health in adolescence -- Cognitive development in adolescence -- Psychosocial development in adolescence -- Glossary -- Bibliography -- Credits -- Name index -- Subject index.
Includes index.
Keywords: 2 -- 0; 6; Child development.;Child psychology.;Adolescence. -- 20; 20; 2